2017
DOI: 10.1093/rheumatology/kex260
|View full text |Cite
|
Sign up to set email alerts
|

The worldwide incidence and prevalence of systemic lupus erythematosus: a systematic review of epidemiological studies

Abstract: There are worldwide differences in the incidence and prevalence of SLE that vary with sex, age, ethnicity and time. Further study of genetic and environmental risk factors may explain the reasons for these differences. More epidemiological studies in Africa are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
417
4
27

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 591 publications
(463 citation statements)
references
References 83 publications
15
417
4
27
Order By: Relevance
“…Interestingly, males are also overrepresented in other immune-mediated neuropathies including the GuillainBarré syndrome (GBS) and multifocal motor neuropathy [9,[37][38][39][40]. The male predominance in these immunemediated neuropathies is unexplained and deviates from female predominance in many classic autoimmune disorders [41][42][43]. A male predominance has also been suggested for other forms of polyneuropathies, suggesting that males are more at risk to develop a polyneuropathy [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, males are also overrepresented in other immune-mediated neuropathies including the GuillainBarré syndrome (GBS) and multifocal motor neuropathy [9,[37][38][39][40]. The male predominance in these immunemediated neuropathies is unexplained and deviates from female predominance in many classic autoimmune disorders [41][42][43]. A male predominance has also been suggested for other forms of polyneuropathies, suggesting that males are more at risk to develop a polyneuropathy [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…SLE affects women more often than men and it is commonly known as the disease of women of childbearing age. 1,2 In a study, to assess the differences between SLE clinics in men and women; men were more affected than women in terms of disability, hypertension, thrombosis, renal and haematological involvement. Women were more likely to have malar rash, photosensitivity, oral ulcer, alopecia, Raynaud phenomenia and arthralgia.…”
Section: Discussionmentioning
confidence: 99%
“…The aetiology of SLE is not fully understood, but both genetic predisposition and enviromental triggers are belived to be involved. 1 In a recent study, the overall age-adjusted incidence and prevalence per 100,000 persons were 5.5 and 72.8, respectively. 2 The incidence and prevalance of SLE is higher in females compared with males regardless of age or ethnic origin.…”
mentioning
confidence: 96%
“…103,104 A second and complimentary model holds that selection pressures due to exposure to pathogens endemic to Africa may account for increased type I IFN production and responses in the AA population. [105][106][107][108] Other population level studies have shown that genetic variants across populations play a major role in shaping an individual's immune response, 109 including variability in cytokine responses to various stimuli. [105][106][107][108] Other population level studies have shown that genetic variants across populations play a major role in shaping an individual's immune response, 109 including variability in cytokine responses to various stimuli.…”
Section: What Drives Transitional B-cell Ifnβ Production?mentioning
confidence: 99%